Treatment of Congenital Factor VII Deficiency with a New Concentrate - Mariani, G; Mannucci, P M; Mazzucconi, M G; Capitanio, A (Thrombosis and Haemostasis, 1978)
A new factor VII concentrate, made from ACD plasma by a process involving successive absorptions of cryoprecipitate supernatant on DEAE Sephadex and of the resulting supernatant on Al(OH)3, was administered to 10 patients with severe factor VII deficiency. 5 patients received only one dose for treatment of a single bleeding episode, the remaining 5 were given multiple infusions (47) for spontaneous hemorrhages or for the prevention of surgical bleeding. In vivo factor VII recovery ranged from 43 to 126% (average 88%) of the assayed in vitro activity of the concentrate. A dose of 0.5 u/kg was found to produce a 1% rise of the plasma factor VII levels. The mean half-life on injected factor VII as assessed in 7 kinetic studies was 205 min (range 168-234). Spontaneous bleeding was easily controlled by the concentrate and major surgical procedures (two tonsillectomies) could be performed without complications. 1 patient developed HBsAg positive hepatitis, but otherwise no serious side effects were observed. Factor VII concentrate reduces the risk of precipitating circulatory overload associated with the use of plasma and avoids the unnecessary rise of factor II, IX and X which follows prothrombin complex concentrates.